Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111). Issue 59 (26th September 2017) - Schwarz, Matthias; Bachmann, Philipp; Silva, Thais Nascimento; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al.
Abstract: Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X‐ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5‐membered ring, leading to the formation of a flat‐lying di‐σ‐indolide in the temperature range from 330–390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6‐membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species. Abstract : Carrying hydrogen : Following a surface science approach, we explore the reaction mechanisms of indole, indoline, and octahydroindole, a potential LOHC system. Combining surface infrared spectroscopy, synchrotron‐based photoelectron spectroscopy, and density functional theory, we identify surface intermediates on Pt(111) and decomposition pathways that may lead to degradation.